Epizody wspólnego zaangażowania biograficznego jako źródło mądrości życiowej - Kuryś-Szyncel , Karolina (Studia Edukacyjne, 2019)
The aim of the article is to introduce the author’s category of joint biographical involvement episodes (EWZB) into the space of educational discourse, especially in relation to adult education (including academic teacher training). The proposed EWZB category derives from the work of Rudolf Schaffer on episodes of joint engagement and is enriched with knowledge on biographical learning. The author notes that one of the volitional goals of adult learning is the desire to acquire wisdom, understood as an aspect of personality development in adulthood, and the basis for building it is learning based on the co-experience of both one’s own and Others’ biographies.